Morbidity and mortality related to type II odontoid fractures in octogenarians undergoing surgery: a retrospective study with 5 year follow up - Lenga, Pavlina; Gülec, Gelo; Kiening, Karl; Unterberg, Andreas; Ishak, Basem (Frontiers in medicine, 2023)
Introduction: The prevalence of trauma is increasing in the geriatric population. The optimal therapy for type II odontoid fractures in the elderly is controversial. This study aims to assess the morbidity and mortality associated with odontoid fractures in octogenarians undergoing C1/C2 posterior screw fixation and describe the perioperative and post-operative complications and risk factors associated with mortality. Materials and methods: Electronic medical records from a single institution pertaining to the period between September 2005 and December 2020 were retrieved. Data on patient demographics, neurological conditions, surgical characteristics, complications, hospital course, and 90-day mortality were collected. Results: Over a 16-year period, 60 patients aged ≥80 years diagnosed with type II odontoid fractures were enrolled in the study. The mean age was 85.0 ± 1.9 years. The mean Charlson Comorbidity Index (CCI) was >6 indicating a poor baseline reserve (8.5 ± 1.9), while cardiovascular diseases were the most prevalent among comorbidities. The mean surgical duration was 217.5 ± 65.9 min, with a mean blood loss of 725.5 ± 275.7 mL. The in-hospital was 5-0% and the 90-day mortality rates increased at 10.0%. No revision surgery was needed in any of the cases. Intraoperative and post-operative X-ray and computed tomography (CT) imaging revealed correct screw placement. Proper alignment of the atlantoaxial spine and fusion could be achieved in all cases. The unique risk factors for mortality included the presence of comorbidities and the occurrence of post-operative complications. Conclusion: The complication and mortality rates associated with odontoid fractures in octogenarians are relatively high. However, the therapeutic goals in this population also include bone union and preservation of neurological status. Despite the often-high comorbidity rate, we still recommend that surgery should be considered in patients over 80 years. However, it is necessary to evaluate several approaches when treating such frail patients.
Gesehen am 21.12.2023